2017
DOI: 10.1038/s41598-017-08204-6
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin, a natural flavonoid, inhibits methylglyoxal induced apoptosis via the mTOR/4E-BP1 signaling pathway

Abstract: Methylglyoxal (MG) accumulation has been observed in human cerebrospinal fluid and body tissues under hyperglycaemic conditions. Recent research has demonstrated that MG-induces neuronal cell apoptosis, which promotes the development of diabetic encephalopathy. Our previous animal study has shown that luteolin, a natural flavonoid, attenuates diabetes-associated cognitive dysfunction. To further explore the neuroprotective properties of luteolin, we investigated the inhibitive effect of luteolin on MG-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…mTOR, a highly conserved serine/threonine kinase, is a central regulator of cell death/survival, protein synthesis, and autophagy . In MLO‐Y4 osteocytes, fluid flow and PGE 2 were reported to activate the Akt/mTOR signals and regulate Hif‐1α expression involved in mechanosensory function .…”
Section: Discussionmentioning
confidence: 99%
“…mTOR, a highly conserved serine/threonine kinase, is a central regulator of cell death/survival, protein synthesis, and autophagy . In MLO‐Y4 osteocytes, fluid flow and PGE 2 were reported to activate the Akt/mTOR signals and regulate Hif‐1α expression involved in mechanosensory function .…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory cytokines induce mitochondrial apoptosis, manifested by the release of the cytochrome C, the suppression of the B cell lymphoma 2 (Bcl-2), the activation of caspases [9,10]. It plays a significant role in neuronal apoptosis in neurodegenerative diseases by integrating death signals through Bcl-2/Bax and coordinates caspases through the release of Cytochrome C. Bcl-2 modulates the translocation of the pro-apoptotic protein Bax from the cytosol to the mitochondrial membrane, where it enhances mitochondrial membrane permeability and releases Cyt C, which further promotes pro-caspases activation [11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the other major regulator in hypoxia is mTOR, which promotes HIF-1α protein activation when hyperactivated (42,43). A previous study indicated that luteolin may inhibit the activation of Mtor (44). Therefore, the negative effect of luteolin and HIF-1α may contribute to the hyperactivation of mTOR.…”
Section: Discussionmentioning
confidence: 99%